1992
DOI: 10.2337/diab.41.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hyperglycemia-Induced Insulin Resistance in Whole Body and Skeletal Muscle of Type I Diabetic Patients

Abstract: To examine the mechanisms of hyperglycemia-induced insulin resistance, eight insulin-dependent (type I) diabetic men were studied twice, after 24 h of hyperglycemia (mean blood glucose 20.0 +/- 0.3 mM, i.v. glucose) and after 24 h of normoglycemia (7.1 +/- 0.4 mM, saline) while receiving identical diets and insulin doses. Whole-body and forearm glucose uptake were determined during a 300-min insulin infusion (serum free insulin 359 +/- 22 and 373 +/- 29 pM, after hyper- and normoglycemia, respectively). Muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 35 publications
5
64
0
Order By: Relevance
“…Hence, the present data suggest that the impaired glycogen synthesis of skeletal muscle from Type 1 diabetic patients in poor metabolic control [1][2][3] is caused by post-translational modifications of the GS enzyme which may be secondary to metabolic derangements [3,7]. This interpretation of results is compatible with the study of Vuorinen-Markkola et al [28] demonstrating that 24 h of hyperglycaemia induces a severe impairment of whole-body non-oxidative glucose metabolism in Type I diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…Hence, the present data suggest that the impaired glycogen synthesis of skeletal muscle from Type 1 diabetic patients in poor metabolic control [1][2][3] is caused by post-translational modifications of the GS enzyme which may be secondary to metabolic derangements [3,7]. This interpretation of results is compatible with the study of Vuorinen-Markkola et al [28] demonstrating that 24 h of hyperglycaemia induces a severe impairment of whole-body non-oxidative glucose metabolism in Type I diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…Studies in both man [1,41,42] and animals [43,44] have shown that sustained hyperglycaemia for as little as 6-24 h induces insulin resistance through a down regulation of the glucose transport system [6,45] both at the level of insulin-independent and insulin-dependent tissues [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…9), forearm glucose uptake was determined under similar conditions of glycaemia and insulinaemia. Reproduced with permission from reference [116] Glucose toxicity -the common acquired cause of insulin resistance in IDDM and NIDDM…”
Section: Is There a Familial Or Genetic Defect In Insulin Action In Rmentioning
confidence: 99%
“…The degree of insulin resistance is inversely correlated with average glycaemic control in both patients with NIDDM [2,112,113] and IDDM [105,114]. Direct proof of the ability of hyperglycaemia per se to induce insulin resistance has been obtained in studies in patients with IDDM [115,116] as well as in studies performed in diabetic …”
Section: Is There a Familial Or Genetic Defect In Insulin Action In Rmentioning
confidence: 99%
See 1 more Smart Citation